Entrepreneurship in Islamic communities: How do Islamic values and Islamic practices influence entrepreneurship intentions?. Issue 5 (28th November 2019) - Rehan, Farooq; Block, Joern; Fisch, Christian
Abstract : Purpose: Prior research has investigated the development of Islamic communities. The authors contribute to this line of research by analyzing the effects of Islamic values and Islamic religious practices on entrepreneurship intentions in Islamic communities. Using theory of planned behavior as a theoretical lens, they also take into account that the relationship between religion and entrepreneurial intentions can be mediated by individual's attitude toward entrepreneurship. Design/methodology/approach: The authors analyze primary data obtained from a sample of 1, 895 Pakistani university students. They also use structural equation modeling to perform a nuanced assessment of the relationship between Islamic values and practices and entrepreneurship intentions and to account for mediating effects. Findings: The results show that both Islamic values and Islamic practices positively influence entrepreneurship intentions. Both effects are mediated by the attitude toward entrepreneurship. Originality/value: The authors contribute to prior research on entrepreneurship in Islamic communities by applying a more fine-grained approach to capture the link between religion and entrepreneurship. Further, they contribute to the literature on entrepreneurship intentions by showing that the influence of religion on entrepreneurship intentions is mainly due to religious values and practices, which shape the attitude toward entrepreneurship and thereby influence entrepreneurship intentions in religious communities.